Harmonization of Parahyangan, Pawongan, and Pabelasan in the Pamalle Ritual: A Study of the Local Wisdom of the Sumbanese Community - Cordia, Grassiana Misseri; I Made Sutajaya; I Wayan Suja; Ida Bagus Made Astawa (MultiTech Publisher, 2024)
The aim of this article is to investigate how the philosophy of Tri Hita Karana (THK) is applied to the